2002
DOI: 10.1002/ajmg.10621
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the clinical and epidemiological complexity of GJB2‐linked deafness

Abstract: GJB2 mutation analysis was performed in 179 unrelated subjects with sporadic or familial hearing loss (HL). Among 57 families, 18 showed a vertical transmission of HL, the disease being present in two or three generations. Besides 155 nonsyndromic cases, 24 patients presenting with extra-auditory clinical signs were included in the molecular study. GJB2 mutation analysis was also performed in 19 subjects with an anamnestic history of perinatal risks factors for acquired HL. The 35delG mutation accounted for 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The hearing impairment associated with GJB2 mutations is frequently severe or profound, but there can be considerable variations among individuals carrying the same mutation, even belonging to the same family [14, 23, 24, 25]. Several observations have reported that mutations in the GJB2 gene may be found in cases with disease of mild or moderate severity [25, 26, 27].…”
Section: Genotype-phenotype Relationship In Gjb2 Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The hearing impairment associated with GJB2 mutations is frequently severe or profound, but there can be considerable variations among individuals carrying the same mutation, even belonging to the same family [14, 23, 24, 25]. Several observations have reported that mutations in the GJB2 gene may be found in cases with disease of mild or moderate severity [25, 26, 27].…”
Section: Genotype-phenotype Relationship In Gjb2 Mutationsmentioning
confidence: 99%
“…Deafness is usually stable, but progression has been reported [23, 26, 28]. Similarly, the hearing deficit is commonly symmetric but asymmetry in the degree of hearing loss between ears has been noticed [25, 29]. Onset is nearly always prelingual, but not necessarily congenital [30].…”
Section: Genotype-phenotype Relationship In Gjb2 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterozygous W44C mutation is present in the extracellular loop E1 (allows the interactions between adjacent cells connexons) of the protein. Other known GJB2 mutations are E47X, I20T, R184P, L90P, delE120 and V95M [81].…”
Section: Page 3 Ofmentioning
confidence: 99%